2008
DOI: 10.1021/om800295z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Ruthenium(IV)-Catalyzed Single and Double Allylation of Indole Compounds using Alcohols as Substrates: Aspects of Ruthenium(IV) Allyl Chemistry

Abstract: 6 ) 2 is shown to be an excellent and rapid catalyst for the C-allylation of indole compounds using allyl alcohols as substrates. Selective, one-pot N,C-double allylation is also possible. Preliminary experiments suggest that vinyl epoxides may be used as an allyl source. Stoichiometric reactions of CH 2 dCHCH(OH)CHdCH 2 , CH 2 dCHCH(OAc)CHdCH 2 , and CH 2 dCHCHdCHCH 2 Br with [Ru(Cp*)(CH 3 CN) 3 ](PF 6 ) afford new Ru(IV) η 3 -vinyl-allyl salts, two of which, [Ru(Cp*)(κ 2 -OAc)(η 3 -vinyl-allyl)](PF 6 ) (13) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 119 publications
2
18
0
Order By: Relevance
“…[11] Often intermedate protonation of allyl alcohol is implicated to increase the reactivity of allyl alcohol for allylation reactions. [10,11,22,23] The strong increase in allylation reaction rate observed with addition of a catalytic quantity of a strong acid such as HOTs (Table 5), can thus be explained by protonation of the allyl alcohol, making H 2 O the better leaving group.…”
Section: Effect Of the Acidmentioning
confidence: 99%
“…[11] Often intermedate protonation of allyl alcohol is implicated to increase the reactivity of allyl alcohol for allylation reactions. [10,11,22,23] The strong increase in allylation reaction rate observed with addition of a catalytic quantity of a strong acid such as HOTs (Table 5), can thus be explained by protonation of the allyl alcohol, making H 2 O the better leaving group.…”
Section: Effect Of the Acidmentioning
confidence: 99%
“…[36 -39] However, thus far for Ru-based catalysts this effect has not been reported; mostly a preference for the branched product is reported, starting from either a branched or a linear allylic substrate. [19,21] The 'memory effect' observed in our experiments indicates that the isomerization of an initially formed branched σ -allyl to a linear σ -allyl species (Scheme 6 from B to D) or vice versa, via the π -allyl species (C) is a relatively slow process relative to reductive elimination (from B to A or D to E). However, in the homoallylic coupling reaction with substrate 7 (Table 4; entry 2), a small amount of branched isomer is also formed, which indicates that a Ru(IV)(π -allyl) species is formed during the catalytic cycle.…”
Section: Mechanistic Considerationsmentioning
confidence: 72%
“…The C3-position apparently is more nucleophilic than the nitrogen atom as has been reported previously. [19] We have shown that indole cannot be allylated with an acidic [CpRu(PPh 3 ) 2 ] + catalyst system, since the acid necessary for activity in allylation is neutralized by indole. [10] Thus, although the indole NH moiety does not seem to coordinate to a Ru(II) species, it is basic enough to be protonated by the strong acid HOTs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations